The effects of gender stereotyping on television towards children / Anis Syahirah Sazali ... [et al.] - Sazali, Anis Syahirah; Zulkifly, Nadira Syarafana; Norzali, Nur Fatini Hanis; Rohmat, Syazanur Husna
The aim of this study is to identify The Effects of Gender Stereotyping on Television towards Children. Effects are things that is caused or produced by something else and can also be defined as consequences or outcomes. Meanwhile, the definitions of gender requires us to ensure that health policy, programmes, services and delivery models are responsive to the needs of women, men, girls and boys in all their diversity. Next is stereotype, stereotype is grouping races or individuals together and make a judgment about them without knowing them. Racial remarks, sexual remarks, and gender remarks are the biggest stereotypes. Next is television, television is a device with a screen that can receive the signal. Television often shows many news, cartoon and films. Last but not least, children can be described as cycle of human life which starts from a children phase then growing up and getting older.